Allelopathy of aconitic acid on soybeans - Voll, Elemar; Garcia, Antônio; Gazziero, Dionisio Luiz Pisa; Adegas, Fernando Storniolo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to determine the effects of aconitic acid on soybean germination and growth. The experiment was carried out under laboratory conditions, in a completely randomized design with 13 soybean cultivars and absence or presence of aconitic acid (2.5 mmol L-1), and agar medium for seed germination. Allelopathic effects vary according to soybean genotypes and may reduce germination, the rate of normal seedlings, stem growth and mainly seedlings root growth.